THE EFFECT OF HERBAL MOUTHWASH (BETEL LEAF) AGAINST HALITOSIS IN ELDERLY - Oktanauli, Poetry (Fakultas Kedokteran Gigi Universitas Prof. Dr. Moestopo (Beragama), 2020)
Background: elderly generally experience a decreased in oral hygiene, number of teeth, mucosal sensitivity of the oral cavity and xerostomia. Xerostomia can cause the decreased in oral hygiene and cause an increase in bad breath (halitosis). One of halitosis therapy that can be done is by using mouthwash. Of the various types of mouthwash on the market, the effectiveness of herbal mouthwash against halitosis is unknown. This research is using herbal mouthwash containing betel leaves, becauseit has an antibacterial, antioxidant and antifungal ability. Purpose : to give information on the benefits of herbal mouthwash on decreasing halitosis score in elderly. Method: this was a clinical experimental research with cross sectional approach. Spearman correlation test was used to determine the effect of herbal mouthwash on decreasing halitosis scores. The numbers of subject were 30 and obtained by quota sampling. Data collection was done by measuring initial and final halitosis score after rinsing with herbal mouthwash (betel leaf), using Tanita breath checker. Tanita breath checker is an innovative palm-sized monitor that can detect and measure the presence of volatile sulfur compound (VSC) by displaying the level of halitosis. Result: the result showed a decrease in halitosis score before and after rinsing with herbal mouthwash (betel leaf). A significant decrease in the halitosis score is indicated by the p=0,000 obtained from the results of the Spearman correlation test. There was a significant decrease in the halitosis score after rinsing with herbal mouthwash. Conclusion: the present study showed that the decrease in halitosis score is due to the betel leaf containing essential oils. The largest content of essential oils is kavikol and betlephenol. Kavikol has an antibacterial power five times stronger than phenol. Thus, herbal mouthwash (betel leaf) can be used as an alternative therapy to overcome halitosis in the elderly.